Obstacles to Heritage Tourism Planning:Socio-spatial Planning Problems within Mardin - Elif GUNDUZ; Rahmi ERDEM (European Regional Science Association (ERSA), 2011)
Mardin represents a distinctive variety of natural and cultural resources. It is considered a major destination for seasonal tourism in Turkey. However, the city suffers from a serious shortage in urban infrastructure necessary for sustainable tourism development. A field survey is carried out to identify the type and range of such problems in relation to the existing infrastructure system. The survey also examines both the role of local community in tourism development and potential revenues. This study analyses the major aspects of such shortages and their effects on tourism sustainability. The paper attempts to present and discuss 1) the effect of inadequate urban infrastructure (roads, waste disposal, and water supply) on the site tourism potential and local standards of living that represent a challenge for sustainable cultural tourism; 2) the role of locals' involvement in tourism development (e.g. safeguarding heritage sites) and in poverty alleviation mechanisms in addition to identifying main heritage assets and related tourism opportunities.
Keywords: 330